2016
DOI: 10.14348/molcells.2016.0232
|View full text |Cite
|
Sign up to set email alerts
|

Viral Inhibition of PRR-Mediated Innate Immune Response: Learning from KSHV Evasion Strategies

Abstract: The innate immune system has evolved to detect and destroy invading pathogens before they can establish systemic infection. To successfully eradicate pathogens, including viruses, host innate immunity is activated through diverse pattern recognition receptors (PRRs) which detect conserved viral signatures and trigger the production of type I interferon (IFN) and pro-inflammatory cytokines to mediate viral clearance. Viral persistence requires that viruses co-opt cellular pathways and activities for their benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…In this study, it was verified that the ATG10 mutants without Cys 44 and Cys 135 also elevated the levels of il28a /IL28a, ifr-3 /IRF-3, and irf-7 /IRF-7. IRF-3 and IRF-7 could induce IFNs expression as interferon regulatory factors ( 46 , 47 ) by nuclear-translocation upon virus infection ( 48 ). In this study, the nuclear translocation and nuclear–cytoplasmic fractionation assays indicated that the ATG10 mutant proteins surprisingly translocated into the nucleus much like the ATG10S protein, but ATG10 and ATG10 ΔM43 did not.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was verified that the ATG10 mutants without Cys 44 and Cys 135 also elevated the levels of il28a /IL28a, ifr-3 /IRF-3, and irf-7 /IRF-7. IRF-3 and IRF-7 could induce IFNs expression as interferon regulatory factors ( 46 , 47 ) by nuclear-translocation upon virus infection ( 48 ). In this study, the nuclear translocation and nuclear–cytoplasmic fractionation assays indicated that the ATG10 mutant proteins surprisingly translocated into the nucleus much like the ATG10S protein, but ATG10 and ATG10 ΔM43 did not.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there exists a need for the viruses to manipulate the host immune surveillance mechanism to facilitate their propagation efficiently [1,8]. Because of this, KSHV encodes for various immunomodulatory proteins, including four vIRFs (vIRF1 to 4) that are homologous to cellular IRFs [17].…”
Section: Resultsmentioning
confidence: 99%
“…These IFNs are upregulated by interferon regulatory factors (IRFs), which serve as transcriptional factors [1]. Among them, IRF3 and IRF7 especially act as direct transducers of viral-mediated type I IFN gene induction.…”
Section: Introductionmentioning
confidence: 99%
“…The KSHV genome encodes four types of viral interferon regulatory factors (vIRFs), vIRF1 to vIRF4, which are homologous to cellular IRFs, which are clustered within one genomic locus ( 18 20 ). Although all vIRFs inhibit both host interferon response and control cellular growth, differences in their activation characteristics result in distinct immune evasion strategies.…”
Section: Introductionmentioning
confidence: 99%
“…This enables efficient lifelong persistence and facilitates the development of KSHV-associated malignancy. Expression of vIRF3 is required for continuous proliferation of PEL cells ( 21 ) and causes dramatic changes in critical host pathways such as apoptosis, cell cycle, antiviral immune response, and tumorigenesis ( 9 , 18 20 ). It was previously shown that vIRF3 (also referred to as LANA-2) is constitutively expressed in B cell lymphotropic diseases, PEL, and MCD but not in KS tumors ( 22 ).…”
Section: Introductionmentioning
confidence: 99%